Quality assurance and the need to evaluate interventions and audit programme outcomes. (29th August 2020) - Zhao, Min; Vaartjes, Ilonca; Klipstein-Grobusch, Kerstin; Kotseva, Kornelia; Jennings, Catriona; Grobbee, Diederick E; Graham, Ian
Abstract: Evidence-based clinical guidelines provide standards for the provision of healthcare. However, these guidelines have been poorly implemented in daily practice. Clinical audit is a quality improvement tool to promote quality of care in daily practice and to improve outcomes through the systematic review of care delivery and implementation of changes. A major priority in the management of subjects with cardiovascular disease (CVD) management is secondary prevention by controlling cardiovascular risk factors and providing appropriate medical treatment. Clinical audits can be applied to monitor modifiable risk factors and evaluate quality improvements of CVD management in daily practice. Existing clinical audits have provided an overview of the burden of risk factors in subjects with CVD and reflect real-world risk factor recording and management. However, consistent and representative data from clinic audits are still insufficient to fully monitor quality improvement of CVD management. Data are lacking in particular from low- and middle-income countries, limiting the evaluation of CVD management quality by clinical audit projects in many settings. To support the development of clinical standards, monitor daily practice performance, and improve quality of care in CVD management at national and international levels, more widespread clinical audits are warranted.